Examining the effects of knowledge, environmental concern, attitudes and cultural characteristics on Kuwaiti consumers' purchasing behavior of environmentally sustainable apparel - Albloushy, Hayat (Kansas State University, 2016)
This study examined the effects of knowledge of apparel and textile (AT) manufacturing’s impacts on the environment, environmental concern, attitudes toward environmentally sustainable apparel (ESA), and the cultural characteristics of adult, female Kuwaiti nationals on purchasing behaviors of ESA. This study was conducted because Kuwait is a large consumer market for apparel goods and there was a gap in the existing literature on sustainable apparel with regards to Kuwait. To measure the independent variables of knowledge related to the environmental impacts of AT manufacturing, environmental concern, attitudes towards ESA, and the cultural characteristics of Kuwaiti women on the dependent variable of ESA purchase behavior intentions, a mixed methods approach was used. This mixed method approach included a survey instrument featuring five different scales to acquire data through quantitative methods on a population of Kuwaitis acquired through snowball sampling. Semi-structured interviews were then utilized to acquire further data for a qualitative data analysis. The results were then analyzed through descriptive statistics, regressions, and coding. The data analysis of the quantitative survey responses of the female Kuwaiti nationals showed that their level of knowledge on the environmental impacts of the AT industry was low, their level of environmental concern was neutral, their ESA attitudes were neutral, and their ESA purchase intentions were slightly positive. Regression results found that environmental concern had no relationship with ESA attitudes, knowledge about AT related environmental issues positively influenced ESA attitudes, and both knowledge about AT related environmental issues and ESA attitudes had a positive influence on ESA purchase intentions. Additionally, the cultural dimensions of the surveyed population showed high power distance and collectivism, low long-term orientation and uncertainty avoidance, and intermediate levels of masculinity and indulgence. The qualitative interview revealed that Kuwaiti culture is strongly influenced by the Islamic religion, and the culture supports high levels of consumerism and ostentatious consumption. A majority of qualitative participants did not express any attitudes toward ESA, and none of the participants had purchased ESA products previously. This could be because female Kuwaiti nationals are limited in their knowledge related to AT environmental risks and are generally unaware of ESA and its purpose. The study’s data could be used to provide educators with information through which to tailor curricula towards the knowledge, attitudes, and beliefs of Kuwaiti nationals. Additionally, this information could be essential for manufacturers and retailers of ESA products, so that they can produce and sell ESA affectively in Kuwait.
Keywords: Environmentally Sustainable Apparel; Kuwaiti Consumer; Kuwaiti Culture; Theory of Reasoned Action; Hofstede Theory of Cultural Dimensions; Environmental Concern